Anatomical organization of the basal ganglia - Parent, Andre (Henry Stewart Talks, 2014)
Subcortical nuclei forming a widely distributed neuronal network, whose integrity is markedly alerted in neurodegenerative diseases, Striatal plasticity due to intrinsic dopaminergic neurons and newly generated neurons opens up new therapeutic avenues for Parkinson’s disease.
Reviewed at 2020/10/14